BOOK REVIEW EN BUSCA DE UNA ESTRATEGIA DE SEGURIDAD NACIONAL (Journal of the Spanish Institute for Strategic Studies, 2018)
ational Security Strategies (NSS) and the institutions associated with them- in the case of Spain, the System, the Council and the Department of NationalSecurity - are recent realities in our country. Although they are still inthe development stage they nevertheless represent a historic step forward.The adjective historic cannot be overemphasised. It is fundamental to theunderstanding of a process involving the two approved NSSs so far. The first of thesewas titled Estrategia Española de Seguridad. Una responsabilidad de todos - SpanishSecurity Strategy. A Responsibility for all- (June 2011, under the Socialist government)and the second: Estrategia de Seguridad Nacional. Un Proyecto compartido - NationalSecurity Strategy. A shared project - (May 2013, under the Popular Party government).Spain, one of the main players - if not the leading actor - in Western society in thesixteenth century, suffered a gradual decline in the seventeenth, recovered to a certainextent in the eighteenth, and went into free fall throughout the nineteenth and partof the twentieth century. The consolidation of democracy has been accompanied byan increase in Spain’s external role consistent with its relative share of power on theinternational stage - we are a medium power - and conditioned by a historical heritagethat still weighs on our political elite and our society. However, viewed from an overallperspective, the trajectory of the last decades is extremely positive.It is also important that programme and institutional development should attractacademic interest. It is further proof of the consolidation of security and defencestudies in Spanish Universities. And it allows for the creation of synergies betweenthe fields of national defence, security and external affairs, and the field of universityresearch and teaching.En busca de una Estrategia de Seguridad Nacional offers an example of that win-winrelationship. Its author, General Miguel Ángel Ballesteros, director of the SpanishInstitute of Strategic Studies, has a long professional background in the Armed Forcesand Defence and also as an academic, which allows him to combine the knowledgeacquired by his practical experience with the rigour of scientific methodology. Thebook based on his doctoral thesis, which received the Extraordinary Doctorate Award,makes a very relevant contribution to the area of security studies and is of interest tothose in political and technical spheres who design and implement national securitystrategies.